Relevansi Pemikiran Pendidikan Syed Muhammad Naquib al-Attas dengan Problematika Pendidikan Modern - Miftahul Jannah; Hera Hapsari Kusuma; Miasari; Aimatul Khoiriyah; Febry Suprapto (Educational Research Center, 2025)
The crisis of modern education, marked by the secularisation of knowledge, moral degradation, and epistemological fragmentation, has generated intellectual anxiety among Muslim scholars. In this context, the educational thought of Syed Muhammad Naquib al-Attas becomes relevant as a paradigmatic alternative that emphasises the integration of knowledge and adab (proper conduct). This study aims to examine the relevance of al-Attas’s educational thought to the problems of modern education, particularly concerning the disorientation of educational aims, the dehumanisation of the learning system, and the dislocation of the meaning of knowledge. The research employs a library-based methodology with a content analysis approach applied to al-Attas’s major works, such as Islam and Secularism, The Concept of Education in Islam, and Prolegomena to the Metaphysics of Islam. The findings indicate that the concept of ta’dīb (education based on adab) proposed by al-Attas serves as an epistemological framework capable of reconstructing the modern educational paradigm towards the unity of knowledge, values, and spirituality. Theoretically, this study contributes to the development of contemporary Islamic educational epistemology, while practically, it offers a new direction for curriculum reform and global educational philosophy that is more oriented towards the formation of the virtuous and civilised human being (insān ādib).